The role of development centers in manager´s education - Hudcová, Šárka (Univerzita Pardubice, 2011)
The paper called „The Role of Development Centres in Managers Education“ is focused on the description of a development centre and the identification of its value for managers’ education. The paper contains a case study describing the implementation of development centres into managers’ education in one of international companies performing in the Czech Republic.
Keywords: development centre; leadership competencies; managers; leaders; education; development